2011
DOI: 10.1007/s10290-011-0112-z
|View full text |Cite
|
Sign up to set email alerts
|

Globalisation, concentration and footloose firms: in search of the main cause of the declining labour share

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 21 publications
4
27
0
Order By: Relevance
“…In addition, Berthold et al (2002) emphasizes the role of globalization on firms' substitution of capital for labor. Oyvat (2010), Schneider (2011), Hutchinson and Persyn (2012), Hogrefe and Kappler (2013) and Elsby et al (2013) confirms the negative effect of globalization with different datasets.…”
Section: Recent Studiessupporting
confidence: 53%
“…In addition, Berthold et al (2002) emphasizes the role of globalization on firms' substitution of capital for labor. Oyvat (2010), Schneider (2011), Hutchinson and Persyn (2012), Hogrefe and Kappler (2013) and Elsby et al (2013) confirms the negative effect of globalization with different datasets.…”
Section: Recent Studiessupporting
confidence: 53%
“…The decline of the labor share of income in many countries has led many researchers to turn to technological progress as an explanation (IMF, 2007a;Bentolila and Saint-Paul, 2003;Arpaia et al, 2009;Driver and Muñoz-Bugarin, 2010;Jones, 2003, Ellis andSmith, 2007;Hutchinson and Persyn, 2009). Specifically, economists draw attention to the ratio between capital and labor measured in efficiency units, which has been steadily increasing since the 1980s (Bental and Demougin, 2010).…”
Section: Technology Did Itmentioning
confidence: 99%
“…The findings of Hutchinson and Persyn (2012) suggest that lower trade costs and factors often associated with economic integration such as international low-wage competition and industry concentration have contributed to the decline in the labour share. One of the recent study conducted by Bassanini and Manfredi (2012) for 25 OECD countries, 20 business-sector industries and covering up to 28 years, indicated that total factor productivity growth and capital deepening jointly account for as much as 80% of the within-industry contraction of the labour share.…”
Section: Introductionmentioning
confidence: 98%